2024
DOI: 10.1161/circresaha.123.322835
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ T-Cell Legumain Deficiency Attenuates Hypertensive Damage via Preservation of TRAF6

Yuhu He,
Pu Zou,
Junmi Lu
et al.

Abstract: BACKGROUND: T cells are central to the immune responses contributing to hypertension. LGMN (legumain) is highly expressed in T cells; however, its role in the pathogenesis of hypertension remains unclear. METHODS: Peripheral blood samples were collected from patients with hypertension, and CD4+ T cells were sorted for gene expression and Western blotting analysis. TLGMNKO (T cell–specific LGMN-knockout) mice (Lgmn f/f … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…Knockdown of TRAF6 blunted the protective effects of LGMN-deficient Tregs after adoptive transfer to hypertensive mice, implicating TRAF6 degradation in LGMN-mediated Treg dysfunction. 1 Taken together, findings by He et al reveal a pathogenic role for LGMN induction in Tregs in hypertension by reducing FOXP3 expression leading to defective immunosuppressive function of these cells (Figure).…”
Section: Article See Pmentioning
confidence: 66%
See 4 more Smart Citations
“…Knockdown of TRAF6 blunted the protective effects of LGMN-deficient Tregs after adoptive transfer to hypertensive mice, implicating TRAF6 degradation in LGMN-mediated Treg dysfunction. 1 Taken together, findings by He et al reveal a pathogenic role for LGMN induction in Tregs in hypertension by reducing FOXP3 expression leading to defective immunosuppressive function of these cells (Figure).…”
Section: Article See Pmentioning
confidence: 66%
“…In additional mechanistic studies, He et al 1 demonstrated that LGMN promotes TRAF6 (Tumor Necrosis Factor Receptor-Associated Factor 6) degradation via chaperone-mediated autophagy. Consistent with prior evidence that TRAF6 promotes NFκB (Nuclear Factor kappa B) activation to induce FOXP3 expression, 3 the loss of TRAF6 resulted in decreased binding of NFκB subunits to the FOXP3 promoter and decreased FOXP3 expression in Tregs.…”
Section: Article See Pmentioning
confidence: 99%
See 3 more Smart Citations